1994
DOI: 10.1111/j.1472-8206.1994.tb00815.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different calcium antagonists and a calcium agonist on the metabolism of propranolol by isolated rat hepatocytes

Abstract: The influence of the dihydropyridine calcium entry blockers nicardipine, amlodipine, nifedipine, isradipine and of the dihydropyridine calcium entry promotor BAY K 8644 on the disappearance rate of propranolol by isolated rat hepatocytes was compared to the effect of diltiazem and verapamil, two non-dihydropyridine calcium channel blockers and known inhibitors of hepatic cytochrome P450 mixed function oxidases. All compounds dose-dependently inhibited the disappearance rate of propranolol. Nicardipine and isra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
6
0

Year Published

1994
1994
2002
2002

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…For example, although nifedipine appears to have little effect on the elimination of CyA in adult renal transplant patients, 8,9 it has been reported to inhibit CYA metabolism in pediatric renal transplant patients. 23 The results of the present study, in addition to the inhibition of propranolol metabolism (CYP2D-mediated) by amlodipine reported by Vercruysse et al 4 …”
Section: Methodssupporting
confidence: 51%
See 4 more Smart Citations
“…For example, although nifedipine appears to have little effect on the elimination of CyA in adult renal transplant patients, 8,9 it has been reported to inhibit CYA metabolism in pediatric renal transplant patients. 23 The results of the present study, in addition to the inhibition of propranolol metabolism (CYP2D-mediated) by amlodipine reported by Vercruysse et al 4 …”
Section: Methodssupporting
confidence: 51%
“…However, such an argument may not always hold for calcium channel blocking drugs. For example, Vercruysse et al 4 reported that the metabolism of propranolol by isolated rat hepatocytes was reduced by 50% when nifedipine was added to a concentration of 30 mM. Although this concentration greatly exceeds plasma concentrations observed in humans or rats, nifedipine causes significant inhibition of propranolol metabolism in vivo in rats.…”
Section: Methodsmentioning
confidence: 94%
See 3 more Smart Citations